(untitled) (JS (JURNAL SEKOLAH), 2022)
Abstract : The Effect of Audio Visual Media on the Ability to Listen to Students’ Stories in Grade IV Elementary School. Listening to a story is an activity of listening and understanding an information or message orally. While the media is an intermediary used to convey information with the aim of providing learning stimuli to students. Therefore, the difficulties that often arise in listening to stories are the difficulty of understanding the meaning in the story and the lack of use of learning media. The purpose of this study was to determine the effect of audio-visual media on the ability to listen to stories of students in grade IV SD Negeri 2 Kelapa. The method used is the true experimental method with the type of control-experiment group design. With a research population of 45 fourth grade students. The research sample was 22 students in the control class with an average final score of 68.86 and 23 students in the experimental class with an average score of 72.39. Collecting research data using a learning outcomes evaluation sheet. Data analysis used independent sample t test. The result of this research is the influence of audio-visual media on listening to stories of students in grade IV SD Negeri 2 Kelapa because tcount > ttable that is (3.076 > 1.681). Keywords: Audio Visual Media and Listening to Stories Abstract : Pengaruh Media Audio Visual Terhadap Kemampuan Menyimak Cerita Siswa Di Kelas IV SD. Menyimak cerita adalah kegiatan mendengarkan dan memahami suatu informasi atau pesan secara lisan. Sedangkan media adalah perantara yang digunakan untuk menyampaikan informasi dengan tujuan memberikan ransangan belajar kepada siswa. Oleh karena itu, kesulitan yang sering muncul dalam menyimak cerita adalah kesulitan untuk memahami makna yang ada dalam cerita dan kurangnya penggunaan media pembelajaran. Tujuan dalam penelitian ini adalah untuk mengetahui pengaruh media audio visual terhadap kemampuan menyimak cerita siswa di kelas IV SD Negeri 2 Kelapa. Metode yang digunakan metode true eksperimen dengan jenis control-eksperiment group desain. Dengan populasi penelitian berjumalah 45 orang siswa kelas IV. Sampel penelitian adalah 22 orang siswa kelas kontrol dengan rata-rata nilai akhir 68,86 dan 23 orang siswa kelas eksperimen dengan rata-rata nilai 72,39. Pengumpulan data penelitian menggunakan lembar evaluasi hasil belajar. Analisis data menggunakan uji independet sampel t test. Hasil dalam penelitian ini adalah adanya pengaruh media audio visual terhadap kemampuan menyimak cerita siswa di kelas IV SD Negeri 2 Kelapa karena thitung > ttabel yaitu (3.076 > 1,681). Kata Kunci : Media Audio Visual dan Menyimak Cerita